Adaptation to Digitalization in Supply Chain Management - Ukolov, Vladimir F.; Shabunevich, Oleg V.; Sysoev, Sergey V. (ExcelingTech, 2020)
Abstract- The purpose of the study was to find out the possibilities of adapting states to global trends in the digital transformation of the main spheres of life for survival and development in an emerging multi-polar world. The work was done as part of a grant from the Russian Foundation for Basic Research and discloses the results of the initial stage of its implementation. Our task was to develop a conceptual vision for solving the problems of adapting states to global trends in digital transformation and to justify the mechanisms for its implementation in practice. Information for the study was compiled from scientific literature, the Internet, statistical reports, and other open sources available for use. In the theoretical part of the study, we needed to clarify such concepts as “digitalization in supply chain management ” and “adaptation”, justify the manifestation of their basic functions, identify and describe such new global trends in digitalization in supply chain management that affect adaptation, as the dominant role of states in this issue over other participants in digital transformations; their massive, comprehensive nature, high speed and irreversibility of digital transformation; recognition of intellectual capital as the undivided dominant power of digital transformation and the displacement of cultural and spiritual factors of human development into the background. Contrary to expectations, we came to the conclusion that the adaptation of states to the global trends of digital transformation in the main areas of life is facilitated by the timely identification, understanding of global changes and the implementation of strategies for adapting institutions, business entities, the population and society to future changes using special rules, mechanisms and decisions set out in the paper. The recommendations arising from this study can be applied at the state and interstate levels of government when developing strategies, programs, regulatory documents, regulations and standards governing adaptation to digitalization in supply chain management. They are useful for business corporations and public organizations which professional interests extend to solving the problems of socialization and adaptation of people, taking into account the diversity of cultures and national identity of citizens.